Incorporating occupancy prediction into indoor air temperature modeling for HVAC system control using LBMPC - Garaza, Christian Rabbi A.; Pedrasa, Jhoanna Rhodette I.; Aswani, Anil J. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
HVAC systems consume up to 40 percent of the electrical power consumption of buildings. This percentage of the total energy consumption of buildings constitute to energy used in maintaining thermal comfort and indoor air quality for the occupants. ASHRAE standards incorporated to rule based control assume maximum occupancy which sacrifices energy efficiency over thermal comfort satisfaction. Much work has been done on integrating binary occupancy information with HVAC control systems. However, occupancy count proves to have an additional effect on the system. Long term Occupant count prediction poses as a solution in exploring future system dynamics of the room temperature as internal heat gain of the room can be attributed to occupant behavior. A long term prediction model for occupant count is developed and scaled to multiple rooms. Indoor temperature model is also developed which takes into account occupancy information to predict the future state of the room temperature. Integration of predicted occupant count with learning based model predictive control (LBMPC) is implemented to determine optimal control action to ensure indoor air temperature requirements. Also, the possibility of maximizing the energy efficiency of the HVAC system while being adaptive to the dynamic occupancy of the room is explored. The main contribution of this work is an occupancy prediction model capable of long-term prediction horizon of up to 4 hours ahead and the integration of occupancy count prediction to indoor air temperature dynamics model. Results show that occupancy count is a significant factor to the indoor air temperature model with a contribution of 0.5488 Kelvin for the maximum occupancy of a graduate student room. While maintaining the indoor temperature within ASHRAE standards, simulations show that LBMPC is capable of energy savings of up to 14.52 percent as compared to the reactive 2 position control scheme.
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman
Keywords: Temperature control; Air conditioning -- Control; Heating -- Control; Ventilation -- Control